Genomic Heterogeneity and Ecological Speciation within One Subspecies of Bacillus subtilis - Kopac, Sarah (American Society for Microbiology, 2014)
Closely related bacterial genomes usually differ in gene content, suggesting that nearly every strain in nature may be ecologically unique. We have tested this hypothesis by sequencing the genomes of extremely close relatives within a recognized taxon and analyzing the genomes for evidence of ecological distinctness. We compared the genomes of four Death Valley isolates plus the laboratory strain W23, all previously classified as Bacillus subtilis subsp. spizizenii and hypothesized through multilocus analysis to be members of the same ecotype (an ecologically homogeneous population), named putative ecotype 15 (PE15). These strains showed a history of positive selection on amino acid sequences in 38 genes. Each of the strains was under a different regimen of positive selection, suggesting that each strain is ecologically unique and represents a distinct ecological speciation event. The rate of speciation appears to be much faster than can be resolved with multilocus sequencing. Each PE15 strain contained unique genes known to confer a function for bacteria. Remarkably, no unique gene conferred a metabolic system or subsystem function that was not already present in all the PE15 strains sampled. Thus, the origin of ecotypes within this clade shows no evidence of qualitative divergence in the set of resources utilized. Ecotype formation within this clade is consistent with the nanoniche model of bacterial speciation, in which ecotypes use the same set of resources but in different proportions, and genetic cohesion extends beyond a single ecotype to the set of ecotypes utilizing the same resources.